Investigation of Aluminum Arsenide Honeycomb Monolayer via Density Functional Theory - Ali, Aqeel Mohsin (Iraqi Journal of Science, 2023)
First principle calculations are performed to theoretically predict the physical properties of hexagonal aluminium arsenide planar and buckled monolayers. The structural characteristics showed that the buckled parameter is about 0.32 A°. Cohesive energies have favourable values and it indicates the fabrication possibility. Phonon dispersion properties indicated that the planar aluminium arsenic monolayers are dynamically unstable, while the buckled is less dynamically unstable. The elastic constant parameters achieved the required characteristics of stable hexagonal monolayer structures. The study of electronic band structure prefers to indirect semiconductor band gaps, and the density of states showed strong orbital hybridization in the conduction band. Planar structure has isotropic light electron effective mass and anisotropic heavy hole effective mass. The buckled structure has isotropic light electron effective mass and isotropic heavy hole effective mass. The absorption spectra have high absorption coefficient in various visible and ultraviolet wavelength. The absorption coefficient levels off at about direct and indirect band gaps.